2010
DOI: 10.4103/0255-0857.66487
|View full text |Cite
|
Sign up to set email alerts
|

A cross-sectional hospital-based study of autoantibody profile and clinical manifestations of systemic lupus erythematosus in south Indian patients

Abstract: Our study was aimed to analyze clinical manifestations, autoantibodies and other serological abnormalities in South Indian patients with systemic lupus erythematosus. Clinical history and findings on systemic examination were noted. Antinuclear antibodies (ANA), antibodies to double-stranded DNA (dsDNA) were detected by immunofluorescence and ANA profile by Immunoblotting. Arthritis was most common followed by fever and skin rash. Clinical manifestations vary according to geographical location of the patient. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
21
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(31 citation statements)
references
References 8 publications
9
21
1
Order By: Relevance
“…Kosaraju K et al and Paul BJ et al among south indian patients also reported that arthritis was the most common manifestation. [9,10] In accordance to this study Kosarju K et al has reported malar rash and vasculitis ulcers not frequently observed. [9] They also mentioned that there is very less observance of raynauds phenomenon.…”
Section: Resultssupporting
confidence: 88%
See 3 more Smart Citations
“…Kosaraju K et al and Paul BJ et al among south indian patients also reported that arthritis was the most common manifestation. [9,10] In accordance to this study Kosarju K et al has reported malar rash and vasculitis ulcers not frequently observed. [9] They also mentioned that there is very less observance of raynauds phenomenon.…”
Section: Resultssupporting
confidence: 88%
“…[9,10] In accordance to this study Kosarju K et al has reported malar rash and vasculitis ulcers not frequently observed. [9] They also mentioned that there is very less observance of raynauds phenomenon. Nephritis is most commonly observed among south east asian patients than in Indian patients.…”
Section: Resultssupporting
confidence: 88%
See 2 more Smart Citations
“…Antibodies data above in GC-positive and GCnegative patients are 140. 5 Conclusion: In this pilot study, there seems to be no difference of GC-like structure in pSS and sSS's salivary glands. GC structure is particularly noted in patients with higher focus score.…”
Section: Referencesmentioning
confidence: 66%